Implementasi Pengembangan Jiwa Entrepreneurship pada Wirausaha Muda Melalui Expopreneur 2024 - Annisa, Rosalina Nur; Salindri, Yerika Ayu; Wulandari, Lastiani Warih; Sudanang, Ertanta Ari; Lestari, Fitri Puji (Universitas Negeri Gorontalo, 2025)
Expopreneur activity is a community service programme that aims to apply the knowledge and practice of entrepreneurship for students. The programme includes an exhibition of food, beverage and service products, as well as competitions and entertainment events, involving students and lecturers. This expo activity is also designed to support the implementation of an independent learning curriculum with a project-based approach. Through entrepreneurial practices, students can develop ideas and innovations in creating products in the field of tourism and hospitality. Developing an entrepreneurial spirit for students can build strong characters, such as independence, creativity, self-confidence, and perseverance. This activity is carried out through the stages of preparation, implementation, evaluation, documentation and publication. The existence of expopreneur activities has proven that student creativity is able to produce significant economic value. This success of the event not only provides financial benefits for students, but also opens wider market opportunities for their products.